Bibliometric study on carbon footprint in aquaculture (Research, Society and Development, 2022)
Carbon footprint is the term that identifies the amount of carbon in the atmosphere emitted by individuals, companies or any type of activity, such as agricultural production. Production chains increasingly need research and actions to mitigate the damage caused to the environment by the emission of greenhouse gases, such as research and actions to adopt methods that sequester these gases from the atmosphere to achieve carbon neutrality. The objective of the article was to carry out a bibliometric study on scientific production, in international journals from the Scopus base, to visualize the trend of research on the topic of carbon footprint and sustainability applied to aquaculture. Research methodology is quantitative, the terms carbon footprint, sustainability and aquaculture were searched in the SCOPUS article base. Research results showed 631 articles, the first article dated 2009 and showed a growing scientific interest in the subject. The conclusion of the study points to the importance of studying solutions to achieve sustainable aquaculture.